El turismo receptivo y su incidencia en el desarrollo económico y social en Huamachuco – provincia de Sánchez Carrión - 2018 - Peña Espinoza, Mishelle Elizabeth (2021)
The research work carried out was based on the District of Huamachuco, Province of Sánchez Carrión, with the main objective of determining whether inbound tourism has an impact on the economic and social development in the Province of Sánchez Carrión - 2018, the research carried out is descriptive , non-experimental, the Inductive-Deductive Method, Hypothetical-Deductive Method was used, data collection and the survey were used as a research technique, to validate the reliability of the data obtained the Cronbach's Alpha method was applied, obtaining 0.834 for the data collection instrument of the receptive tourism variable and 0.852 for the economic and social development variable; The population consisted of 1200 residents of the district of Huamachuco - Sector Fatima who are of working age, a representative sample was obtained through the statistical method of 133 inhabitants, to whom the data collection instrument was applied, and with the Information obtained could meet the objectives of the research, test the hypothesis, and make recommendations to develop receptive tourism with the purpose of improving economic and social development in Huamachuco, obtaining as a main result that the study variables are positively related , with a Pearson correlation coefficient equal to 0.77, and as a result of the correlational analysis of the variables, it was concluded that receptive tourism has a positive impact on economic and social development for the inhabitants of the district of Huamachuco.